The Emerging Role of microRNAs in Polyglutamine Diseases - Dong, Xiaoyu; Cong, Shuyan (Frontiers in Molecular Neuroscience, 2019)
MicroRNAs (miRNAs) are small non-coding molecules that regulate a large number of genes for post-transcriptional repression by recognizing semi-complementary target sequences that are usually located in the 3′ UTR sequence of the mRNA. Altered miRNA expression has been associated with several pathological processes, including polyglutamine (Poly Q) diseases. Specific expression patterns in the brain parenchyma and circulating fluids have been highlighted as potential biomarkers for Poly Q disease diagnosis and prognosis. Several miRNAs have been consistently identified in various diseases, including Huntington’s disease (HD) and spinocerebellar ataxia (SCA). In this review, we describe the emerging role of miRNAs in Poly Q diseases and provide an overview on general miRNA biology, implications in pathophysiology, and their potential roles as future biomarkers and applications for therapy.